Spatial Analysis of Land Use Deviations in Sirimau Sub-district, Ambon City Based on Cultivation and Protected Areas, Ambon City Spatial Plan 2011-2031 - Hehanussa, Fekry Salim; Rakuasa, Heinrich (Yayasan Adra Karima Hubbi, 2024)
This study conducts a spatial analysis of land use deviations in the Sirimau Sub-district of Ambon City, focusing on the impacts of urbanization and population growth on the implementation of the Ambon City Spatial Plan (RTRW) 2011-2031. Utilizing remote sensing and GIS techniques, the research identifies significant discrepancies between planned and actual land use, driven by economic pressures and ineffective enforcement of land use regulations. The findings reveal that the conversion of agricultural land and protected forests into residential areas poses serious threats to environmental sustainability and biodiversity. The study emphasizes the need for enhanced community involvement, better inter-agency coordination, and stricter regulatory enforcement to address these challenges and promote sustainable land use practices in the region.